Pengaruh Kondisi Keuangan Perusahaan, Kualitas Audit dan Opinion Shopping Terhadap Penerimaan Opini Going Concern - Rahim, Syamsuri (Jurnal Ilmiah Akuntansi dan Bisnis, 2017)
This study aims to examine the effect of the company’s financial condition, the audit quality and shopping opinion towards the acceptance of going concern audit opinion. The samples used in this research are manufacturing companies listed in Indonesia Stock Exchange in 2012-2014. The population of this study is132. The samples used are 28 companies selected by random sampling method during the observation period of 3 (three) years. Data was analyzed using logistic regression analysis model. The results show that the financial condition, audit quality and opinion shopping significantly influence the acceptance of going concern audit opinion.
Keywords: going concern opinion, financial condition,quality of audits, opinion shopping